2016
DOI: 10.1159/000444855
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3 Like-1: An Emerging Molecule Involved in Diabetes and Diabetic Complications

Abstract: Chitinase 3 like-1 (CHI3L1) is a chitinase-like protein member of family 18 chitinases, expressed in innate immune cells and involved in endothelial dysfunction and tissue remodelling. Since CHI3L1 is highly expressed in a variety of inflammatory diseases of infectious and non-infectious aetiology, it is recognised as a non-invasive prognostic biomarker for inflammation. A variety of studies revealing the increase in CHI3L1 levels in obesity, insulin resistance and in pathological conditions, such as atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 138 publications
(187 reference statements)
0
31
0
Order By: Relevance
“…In line with these findings, both mRNA and protein expression levels of CHI3L1 were significantly increased in OVA‐sensitized WT mice compared to control WT mice. Numerous studies have shown elevated serum levels of YKL‐40 to be correlated with disease severity, and with poorer outcomes for many diseases, including cancer, psoriasis, rheumatoid arthritis, type 2 diabetes, liver fibrosis, atherosclerosis and coronary artery disease . CHI3L1 is considered a risk factor gene for allergic diseases and has polymorphisms which correlate with asthma prevalence and abnormal lung function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, both mRNA and protein expression levels of CHI3L1 were significantly increased in OVA‐sensitized WT mice compared to control WT mice. Numerous studies have shown elevated serum levels of YKL‐40 to be correlated with disease severity, and with poorer outcomes for many diseases, including cancer, psoriasis, rheumatoid arthritis, type 2 diabetes, liver fibrosis, atherosclerosis and coronary artery disease . CHI3L1 is considered a risk factor gene for allergic diseases and has polymorphisms which correlate with asthma prevalence and abnormal lung function .…”
Section: Discussionmentioning
confidence: 99%
“…to be correlated with disease severity, and with poorer outcomes for many diseases, including cancer, psoriasis, rheumatoid arthritis, type 2 diabetes, liver fibrosis, atherosclerosis and coronary artery disease. 9,13,33,34 CHI3L1 is considered a risk factor gene for allergic diseases and has polymorphisms which correlate with asthma prevalence and abnormal lung function. 35 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase 3-like-1 (Chi3L1), also called a breast regression protein 39 (BRP-39) in mouse and YKL-40 in human, is known as a secreted glycoprotein and prototypic mammalian chitinase like protein [11,12]. Increased expression of Chi3L1 protein and mRNA have been shown in various disease models and states including rheumatoid arthritis schizophrenics, inflammatory bowel disease, chronic obstructive pulmonary disease, asthma, diabetes, and atherosclerosis [13][14][15][16][17][18][19], Especially, Chi3L1 expression has been found in a variety of cancer cells such as breast, lung, prostate, colon, rectum, ovary, kidney, breast, glioblastomas, and malignant melanoma [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pro-in ammatory cytokines such as IFN-γ, TNF-α, IL-1β, and IL-6 are involved in the expression of CHI3L1 [20]. The excessive increase in CHI3L1 can have unpredictable pathological effects by initiating and persisting chronic in ammation [21]. Several clinical studies reported that the elevation of CHI3L1 was observed in patients suffering from a wide range of diseases: cancer, metabolic, and neurological diseases [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%